Preparation of the Future Music Teacher to Instrumental-Performing Activity - Yarova, Maryna (Pedagogical Discourse, 2012)
Theoretical approaches to consideration of question of instrumental-performing preparation and determination of the role of this process in professional development of the future music teacher are described in the article.